Influence of Ga3+ ion dopant on the structure and magnetic properties of YCrO3. Issue 17 (1st December 2020) - Shi, Chenfei; Su, Yuling; Guo, Jinjin; Gong, Gaoshang; Hu, Huiyun; Gao, Yawei; Wang, Yongqiang
Abstract: In this work, Ga 3+ doped YCr1- x Ga x O3 ( x  = 0, 0.1, 0.2 and 0.3) polycrystalline samples were prepared by solid state reaction method and their crystal structure, morphology, internal defect, specific heat and magnetic properties were studied. The results show that the lattice constants, lattice volume and particle size increase, while Y/Cr–O bond constant decreases with replacing Cr 3+ by Ga 3+ . The positron annihilation spectrum (PAS) measurement shows that cation vacancy defect exists in all samples and the internal defect concentration fluctuates slightly with increasing of Ga 3+ ions doping concentration. For low doping content, an additional magnetization anomaly emerges in the zero-field-cooling curves measured in H  = 1000Oe. With the increase of magnetic field, the anomaly can be well suppressed. Simultaneously, for the specific heat curve peak cannot be observed at the corresponding temperature. These results imply the establishment of short-range magnetic order above the antiferromagnetic transition temperature ( T N ) due to the dilution effect of nonmagnetic Ga 3+ doping.